Body Shame pada Siswa - Tita Rosita; Rima Irmayanti; Heris Hendriyana (Journal of Innovative Counseling : Theory, Practice, and Research, 2019)
This study aims to describe the students’ body shame in class X students at SMAN 5 Cimahi. Body shame is a person's shame in one part of his body and this often occurs during puberty in early adolescence, because in early adolescence many changes in body shape began. This study uses a survey method. The population in this study were students of SMAN 5 Cimahi with a total of 341 people, 150 male students and 191 female students. The sampling technique in this study is nonprobability sampling, so that the sample in this study were all students of class X SMAN 5 Cimahi. The results showed that the level of body shame of all class X students of SMAN 5 Cimahi showed that the highest percentage aspect was criticizing the appearance of others without the knowledge of the person. Then, the next category is the aspect of criticizing the appearance of others in front of the person. The aspect of criticizing one's own appearance through assessment or comparison with other people has a low category compared to other aspects. The description of the profile of body shame based on sex, namely the aspect of criticizing the appearance of others without the knowledge of the person has a high percentage of male students 64% and in the same aspect the low percentage is 36%; 58% female students and in the same aspect the low percentage is 42%.